1995
DOI: 10.1121/1.414306
|View full text |Cite
|
Sign up to set email alerts
|

Production and perception of consonant coarticulation in Taiwanese

Abstract: Taiwanese coda stop consonants are unreleased, so that their place of articulation tends to be confused with that of the initial consonant of any following syllable. This traditionally is described as place assimilation–i.e., categorical feature change. Recent phonetic theories suggest an alternative description in terms of a continuous variation in degree of coarticulatory overlap between consonants. This study investigates the production and perception of coda consonants before different following onset cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous EPG (electropalatography) study (1) investigating place coarticulation in Taiwanese dental-velar or velardental stop sequences separated by word boundaries (/pat#kag/, Ipa@khagl, /lakMa@, fiak%ha~showed that the timing of the two place gestures was affected by speech rate. The latency of the second gesture relative to the first gesture decreased as speech rate increased.…”
Section: Backgro~dmentioning
confidence: 99%
“…Previous EPG (electropalatography) study (1) investigating place coarticulation in Taiwanese dental-velar or velardental stop sequences separated by word boundaries (/pat#kag/, Ipa@khagl, /lakMa@, fiak%ha~showed that the timing of the two place gestures was affected by speech rate. The latency of the second gesture relative to the first gesture decreased as speech rate increased.…”
Section: Backgro~dmentioning
confidence: 99%